The relationship between cork oak growth patterns and soil, slope and drainage in a cork oak woodland in Southern Portugal - Costa, Augusta; Madeira, Manuel; Oliveira, Ângelo Carvalho (Forest Ecology and Management, 2008)
The inﬂuence of soil type, slope and drainage on tree growth patterns (density, tree size, crown canopy cover and cork yield) was assessed in a cork oak montado, located in Central-western Portugal, based on a GIS approach followed by ﬁeld survey. Five soil groups, that is, Arenosols, Regosols, Podzols, Luvisols and Gleysols, combined in three slope classes (ﬂat, undulating and steep) under two different hydromorphic conditions (normal or deﬁcient) were compared based on ﬁve cork oak stand parameters using ANOVA and PCA tests. The results showed a clear inﬂuence of soil type on cork oak growth patterns (cork yield, basal area, number of trees per hectare, crown canopy cover and circumference at breast height). In Arenosols all parameters showed maximum values and, in contrast, in Gleysols were found the minimum values. For instance, the average of the annual cork production for Gleysols (153 kg ha 1 year 1 ) was only 70% of the expected annual cork production of Arenosols (219 kg ha 1 year 1 ) and the average exploited tree density decreased from 56 trees ha 1 in Arenosols to 44 trees ha 1 in Gleysols, for an average exploited tree density of 53 trees ha 1 for the study area. Slope also seems to inﬂuence the cork oak growth patterns, as signiﬁcant statistical differences were found for cork oak growth parameters between slope classes: steep slopes decreased the cork production, the tree size (circumference at breast height) and the tree density. An overall PCA test showed that three main soil groups could be identiﬁed: (i) Arenosols and Podzols; (ii) Regosols and (iii) Luvisols and Gleysols, showing that the former, which could allow the tree root development, have a positive inﬂuence on the cork oak growth. A two-way analysis of variance, for soil type and slope, showed that the cork yield and the exploited tree density are clearly affected by these two factors interaction.
Keywords: cork yield; drainage; montado; Quercus Suber L; slope; Soil; tree density

The relationship between cork oak growth patterns and soil, slope and drainage in a cork oak woodland in Southern Portugal - Costa, Augusta; Madeira, Manuel; Oliveira, Ângelo Carvalho (Forest Ecology and Management, 2008)
The inﬂuence of soil type, slope and drainage on tree growth patterns (density, tree size, crown canopy cover and cork yield) was assessed in a cork oak montado, located in Central-western Portugal, based on a GIS approach followed by ﬁeld survey. Five soil groups, that is, Arenosols, Regosols, Podzols, Luvisols and Gleysols, combined in three slope classes (ﬂat, undulating and steep) under two different hydromorphic conditions (normal or deﬁcient) were compared based on ﬁve cork oak stand parameters using ANOVA and PCA tests. The results showed a clear inﬂuence of soil type on cork oak growth patterns (cork yield, basal area, number of trees per hectare, crown canopy cover and circumference at breast height). In Arenosols all parameters showed maximum values and, in contrast, in Gleysols were found the minimum values. For instance, the average of the annual cork production for Gleysols (153 kg ha 1 year 1 ) was only 70% of the expected annual cork production of Arenosols (219 kg ha 1 year 1 ) and the average exploited tree density decreased from 56 trees ha 1 in Arenosols to 44 trees ha 1 in Gleysols, for an average exploited tree density of 53 trees ha 1 for the study area. Slope also seems to inﬂuence the cork oak growth patterns, as signiﬁcant statistical differences were found for cork oak growth parameters between slope classes: steep slopes decreased the cork production, the tree size (circumference at breast height) and the tree density. An overall PCA test showed that three main soil groups could be identiﬁed: (i) Arenosols and Podzols; (ii) Regosols and (iii) Luvisols and Gleysols, showing that the former, which could allow the tree root development, have a positive inﬂuence on the cork oak growth. A two-way analysis of variance, for soil type and slope, showed that the cork yield and the exploited tree density are clearly affected by these two factors interaction.
Keywords: cork yield; drainage; montado; Quercus Suber L; slope; Soil; tree density

FITOMASA SUBTERRÁNEA Y AÉREA EN PASTOS DE DEHESA - Puerto Martín, A; Puerto, A (Pastos, 1992)
A study has been conducted on the spatial variations undergone by root biomass, aerial phytomass and the root/shoot ratio in grassland communities (dehesa systems). These variations are governed by the prevailing gradients: topographic and the effect of the tree canopy. The greatest biomass, both underground and aerial, and the lowest root/shoot ratio are usually found in the more fertile sites (deposition sector of slope) and shaded áreas (under the crowns of the trees), in contrast to the results of some researchs performed in cultures or at the laboratory. In the case of natural or semi-natural groupings of herba- ceous species in severe environments, the adaptive responses of each species appear to predomínate over any generalized type of response. Key
Keywords: España; fitomasa; Grasslands; influencia del arbolado; ladera; pastos; phytomass; Salamanca; Salamanca (Spain); slope; tree canopy ¡nfluence

Ecological succession in oligotrophic pastures of central Spain - Pineda, F D; Nicolas, J P; Rou, A; Galiano, E F (Plant Ecology, 1981)
The dynamics of oligotrophic pastures were analyzed in the area of El Pardo (Central Spain), and related with geomorphological features and time elapsed since the last ploughing. A sampling of the area was carried out regarding these two factors. The data were subjected to correspondence analysis, which showed the progressive replacement of species related to succession, variation along slopes, with a tight interaction between both phenomena. The correspondence between vegetation change and slope geomorphology is closer as succession progresses.
Keywords: Central Spain; correspondence analysis; geomorphology; grassland; slope; succession